Spoiler effects reduction with using active power filter on a direct torque controlled induction machine - Aliskan, Ibrahim; Gulez, Kayhan; Altun, Yusuf (Tubitak Scientific & Technological Research Council Turkey, 2011)
Harmonics, which may be placed in electrical systems, have important effects on performance parameters of electrical motors. In this paper, effects of electrical power system voltage harmonics On torque position of induction motors are dealt with. System modeling with Pulse Width Modulation (PWM) type Active Power Filter (APF) is used for reducing these effects. APF, as a subsystem, is placed into torque control system entrance to save the control system and induction motor output torque. Motor outputs, that are before-after A PP connections, are handed for understanding effects of voltage harmonics. Since APF design was based on voltage harmonics; Electromagnetic Interference (EMI) has not changed. Main. goal of the filter is zero effect of voltage harmonics on motor torgue. A new place is selected for APF and the filter control system is designed with using Lyapunov function at the same time. Classical PI controlled APF is used like as a reference filter system and final result is that motor and system elements are defended by nonlinear controlled APF.
Keywords: Nonlinear control; Lyapunov theory; active power filter; direct torque control; CONVERTER; Computer Science; Engineering